Naskah Chujjatu Ash-Shiddîq Li Daf’i Az-Zindîq Karya Nuruddin Ar-Raniri (Kajian Filologi): Chujjatu Ash-Shiddîq Li Daf'i Az-Zindîq Written By Nuruddin Ar-Raniri (Philological Study) - Ferawati (Universitas Ahmad Dahlan, 2022)
This research aims to analyze the physical and content of the Chujjatu As-Siddiq Li Daf`I Zindiq manuscript. The method used is the critical edition, namely editing the script by correcting some errors and irregularities, while the spelling is adjusted according to applicable regulations. There were word groupings, sentence divisions, and capital letters used as well as comments were also given regarding the text errors. Proper corrections are made based on perfect understanding as a result of comparisons between similar, and contemporary manuscripts. The manuscript written by Nuruddin Ar-Raniri has two versions, namely, script A and script B. The complete contents are 27 pages and talk about